A Generalized Multiconductor Transmission Line Model and Optimized Method for the Solution of the MTL Equations - Chaoqun Jiao; Zhanjun Xia; W. N. Fu (International Journal of Antennas and Propagation)
A generalized multiconductor transmission line (MTL) model is developed for modeling of wide frequency transient response on busbars, cables and core-type transformer windings. Different from the traditional MTL model, the equations of the generalized MTL model are built in the cylindrical coordinate system beside rectangular coordinate system. Based on further discussion, it is found that generalized MTL model could be changed to MTL model where all lines have the same length as to the core-type transformer windings. Then, the optimized solution based on Time domain finite element method (TDFEM) is developed for the above MTL equations. It avoids numerical oscillation of the finite difference time domain (FDTD) method. The numerical results are in agreement with ones calculated by Bergeron's method and FDTD method.